2006
DOI: 10.1002/dvdy.20729
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin is a novel marker of pancreatic ductal tissues and of undifferentiated pancreatic precursors in mice

Abstract: Matricellular proteins mediate both tissue morphogenesis and tissue homeostasis in important ways because they modulate cell-matrix and cell-cell interactions. In this study, we found that the matricellular protein osteopontin (Opn) is a novel marker of undifferentiated pancreatic precursors and pancreatic ductal tissues in mice. Our analysis also underscored a specific, dynamic profile of Opn expression in embryonic pancreatic tissues that suggests the participation of this protein's function in processes inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 34 publications
2
25
0
Order By: Relevance
“…To confirm protein expression, 3-wk-old Ring colonies were handpicked, pooled, fixed, and analyzed by whole-mount or frozensection immunofluorescent staining and confocal imaging. Consistent with the microfluidic qRT-PCR analysis, ductal protein marker expression was present in all colonies examined, and each colony was positive for ductal proteins, Sox9/EGFP, Mucin1, or Osteopontin1 (Spp1) (52) (Fig. 1E).…”
Section: Sox9/egfpsupporting
confidence: 78%
“…To confirm protein expression, 3-wk-old Ring colonies were handpicked, pooled, fixed, and analyzed by whole-mount or frozensection immunofluorescent staining and confocal imaging. Consistent with the microfluidic qRT-PCR analysis, ductal protein marker expression was present in all colonies examined, and each colony was positive for ductal proteins, Sox9/EGFP, Mucin1, or Osteopontin1 (Spp1) (52) (Fig. 1E).…”
Section: Sox9/egfpsupporting
confidence: 78%
“…S4D in the supplementary material), whereas OPN also marks endocrine cells (Kilic et al, 2006; data not shown). Our findings show that, especially during development, presumed ductal markers are not expressed in identical cellular domains, implying that these domains could differ in their developmental potential.…”
Section: Research Articlementioning
confidence: 80%
“…Overexpression was performed by adenoviral transduction of HNF6 (Ad-HNF6) or Sox9 (Ad-Sox9), with GFP-expressing adenovirus (Ad-GFP) as a control. In the acinar 266-6 cell line, expression of HNF6 (but not of GFP or Sox9) induced Sox9, CK19 and osteopontin30 which, in the pancreas, have an expression restricted to the ductal cells, and repressed the acinar markers Mist1, Ptf1a, amylase, CPA and elastase (figure 2A). HNF1β was weakly induced by HNF6 (figure 2A).…”
Section: Resultsmentioning
confidence: 99%